2018
DOI: 10.5032/jae.2018.01153
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Self-Regulated Learning in Online Agriculture Courses

Abstract: For students to be successful in the online learning environment, change from passive learners to active learners is essential. Students who successfully regulate and change their learning know where and how to acquire the knowledge necessary for success in the online environment. Introducing students early through dual enrollment programs can ensure students have the necessary skills for success. This project sought to determine the self-regulated learning level of students in an online agriculture course. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…As a reason, live lessons are recorded in online education, which enables the students to watch the lessons later where they miss a class, and to easily repeat the lessons asynchronously at any time and as many times as they want irrespective of whether they miss a class or not. To the contrary of the findings of this study, Chumbley et al (2018) found that "structuring the environment" and "goal setting" were associated with a high level of self-regulated skills in online courses. The above-mentioned difference between the finding of this study and the finding of Chumbley et al's study may be attributed to various factors such as the learning environment designed by the individual, the environment created by the teacher for the online course, technology literacy, ICT skills, and material barriers arising from the teaching environment that hinder learning.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As a reason, live lessons are recorded in online education, which enables the students to watch the lessons later where they miss a class, and to easily repeat the lessons asynchronously at any time and as many times as they want irrespective of whether they miss a class or not. To the contrary of the findings of this study, Chumbley et al (2018) found that "structuring the environment" and "goal setting" were associated with a high level of self-regulated skills in online courses. The above-mentioned difference between the finding of this study and the finding of Chumbley et al's study may be attributed to various factors such as the learning environment designed by the individual, the environment created by the teacher for the online course, technology literacy, ICT skills, and material barriers arising from the teaching environment that hinder learning.…”
Section: Discussioncontrasting
confidence: 99%
“…There is substantial evidence in the literature that individuals with goal-setting skills set a wide array of goals for themselves in various dimensions whether in relation to their personal lives or their careers and that such individuals use web-based teaching learning environments more effectively (Milligan and Littlejohn, 2016). Similarly, Chumbley et al (2018) found that there is a highly significant relationship between goal setting and self-regulation skills with respect to web-based education. Additionally, Kizilcec, Pérez-Sanagustín and Maldonado (2017) reported goal setting and strategic planning skills as predictors of students' reaching their personal goals, whereas Jo, Tomar, Ferschke, Rose and Gasevic (2016) revealed that students who set achievable goals for themselves use the MOOC (Massive Open Online Courses) online learning platform for a longer time, and actively participate in activities.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing need for research targeted at online education (Chumbley, Haynes, Hainline, & Sorensen, 2018). This is especially true when considering how in a matter of months a global pandemic such as COVID-19 was able to radicalize the consistency of "education" and force students and educators worldwide to adapt to distance-based learning.…”
Section: Discussionmentioning
confidence: 99%
“…In the perspective of distance education, self-regulation refers to learners' capability to control and manage their learning events in a distance learning atmosphere without a face-to-face instructor's assistance (Lock et al, 2017). Learners need to establish their targets initially in distance learning practices and assess the progress made to achieve the targets after completing the practices (Chumbley et al, 2018). Learners who achieve progress in distance education atmosphere utilize self-regulation strategies (Marsteller & Bodzin, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%